Pregnancy complications and placental histology following embryo transfer with a thinner endometrium. Issue 8 (30th June 2022) - Ganer Herman, Hadas; Volodarsky-Perel, Alexander; Ton Nu, Tuyet Nhung; Machado-Gedeon, Alexandre; Cui, Yiming; Shaul, Jonathan; Dahan, Michael H
Abstract: STUDY QUESTION: Are deliveries following IVF with a thinner endometrium associated with adverse perinatal outcomes and placental findings? SUMMARY ANSWER: Live births following IVF with a thinner endometrium are associated with an increased rate of placental-mediated obstetric complications and lower birthweight, while the placentas are notable for gross anatomical and histological malperfusion lesions. WHAT IS KNOWN ALREADY: Past studies have noted a higher rate of adverse outcomes on deliveries following IVF with a thinner endometrium, mainly placental-associated complications. However, no study to date has investigated placental histopathology in such cases. STUDY DESIGN, SIZE, DURATION: This was a retrospective cohort study of 1057 deliveries following IVF, between 2009 and 2017. All placentas were sent to pathology irrelevant of pregnancy complication status, per protocol at our institution. PARTICIPANTS/MATERIALS, SETTING, METHODS: Live singleton births from a tertiary university hospital after IVF were compared between patients for whom embryo transfer was performed with an endometrium <9 mm (thinner endometrium group) and patients with an endometrium ≥9 mm (control group). Placental pathologic findings were categorized according to the Amsterdam Placental Workshop Group Consensus. Outcomes were placental findings, including anatomic, inflammatory, vascular malperfusion and villous maturation lesions, as well as obstetric and perinatal outcomes. Continuous and categorical variables were compared as appropriate, and multivariate regression and linear analyses were employed to control for confounders. MAIN RESULTS AND THE ROLE OF CHANCE: A total 292 cases in the thinner endometrium group, and 765 in the control group were compared. Maternal demographics were non-significant between the groups, except for main fertility indication was more commonly diminished reserve in patients with a thinner endometrium and less commonly male factor, P  = 0.003. Higher rates of fresh transfers were noted in the control group, while the thinner endometrium group was notable for higher rates of blastocyte transfers. After adjustment for confounders, deliveries in the thinner endometrium group were associated with an overall higher rate of main placental-mediated complications, 22.9% versus 15.2%, P  = 0.003, and significantly lower birthweight, β −100.76 g (−184.4–(−17.0)). Placentas in the thinner endometrium group were notable for reduced thickness and a higher rate of bilobated placentas. Placental histology in the thinner endometrium group demonstrated a higher rate of maternal malperfusion lesions. LIMITATIONS, REASONS FOR CAUTION: The study was limited by its retrospective design and lack of data regarding prior uterine surgery. In addition, sample size was limited for detection of differences in outcomes of rarer occurrence and for analysis as per a stricter definition of thin endometrium. WIDER IMPLICATIONS OF THE FINDINGS: Excess obstetric risks should be taken into consideration while planning an embryo transfer with a thinner endometrium. Further studies are needed to assess the yield of cycle cancellation and the effect of potential preventive measures such as Micropirin treatment. STUDY FUNDING/COMPETING INTEREST(S): No funding was used and the authors report no conflicting interests. TRIAL REGISTRATION NUMBER: N/A.